2019
DOI: 10.1016/j.jpsychores.2019.109736
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in children with medically unexplained symptoms: a systematic review

Abstract: Objective: Adult research investigating the link between alexithymia and medically unexplained symptoms (MUS) has found a significant relationship between increased alexithymia and MUS. This difficulty in expressing emotions is likely to begin in childhood so the objective of this paper is to present a quantitative review of studies focussing on the association between MUS and alexithymia in children. Methods: Databases were searched with predefined terms relating to alexithymia and MUS in children (0-17 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
2
9
0
1
Order By: Relevance
“…Removal of the EOT and reverse-coded items from the model greatly improved overall fit, but three additional items needed to be removed in order to meet our a priori standards of adequate IRT model fit and negligible I-DIF by diagnostic group. The final TAS-8 short form consisted of five DIF items [1,6,9,13,14] and three DDF items [2,11,12] that ostensibly form the core of the "general alexithymia" construct measured by the TAS-20 total score. Using item response theory, we generated norm-referenced TAS-8 scores that are immediately interpretable on the scale of a Z-score (i.e., M = 0, SD = 1) and can similarly be scaled to the familiar T-score metric (M = 50, SD = 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the EOT and reverse-coded items from the model greatly improved overall fit, but three additional items needed to be removed in order to meet our a priori standards of adequate IRT model fit and negligible I-DIF by diagnostic group. The final TAS-8 short form consisted of five DIF items [1,6,9,13,14] and three DDF items [2,11,12] that ostensibly form the core of the "general alexithymia" construct measured by the TAS-20 total score. Using item response theory, we generated norm-referenced TAS-8 scores that are immediately interpretable on the scale of a Z-score (i.e., M = 0, SD = 1) and can similarly be scaled to the familiar T-score metric (M = 50, SD = 10).…”
Section: Discussionmentioning
confidence: 99%
“…These individuals also tend to exhibit a reduction in imaginal processes and a stimulus-bound, externally oriented style of thinking (i.e., "concrete thinking"). Alexithymia is not itself considered a psychiatric diagnosis; rather, the condition can better be described as a dimensional personality trait that is expressed to varying degrees in the general population and associated with a host of medical, psychiatric, and psychosomatic conditions [2][3][4][5][6][7][8][9][10][11][12][13][14]. Although there is taxometric evidence to suggest that alexithymia is a dimensional rather than categorical construct [15][16][17], researchers frequently categorize a portion of individuals as having "high alexithymia" based on questionnaire scores above a certain threshold, with upwards of 10% of the general population exceeding these thresholds [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Given that patients with alexithymia are not expected to fully understand that physical symptoms can be somatic representations of emotions, they are considered to be more likely to falsely attribute physical signs to physical illness and to request medical attention for symptoms with no underlying medical cause. Therefore, alexithymia is known to be a predisposing and persistent factor in the occurrence of MUPS, contributing to one of the somatoform disorders [ 10 , 11 ]. Various studies, usually non-clinical trials, have reported a correlation between alexithymia and multiple somatization interventions.…”
Section: Introductionmentioning
confidence: 99%
“…First, in the adult population, alexithymia is significantly associated with FND (Demartini et al, 2014); in particular, our group previously hypothesized that functional symptoms might arise when adult individuals with alexithymic and obsessive-compulsive personality traits might fail to interpret correctly as anxiety or panic the autonomic arousal occurring during a physical precipitating event and might interpret these sensations as symptoms of physical illness. A recent systematic review about alexithymic traits in children with Medically Unexplained Symptoms (MUS, including pain, tension-type headache, functional abdominal pain, headache and Chronic Fatigue Syndrome) showed that alexithymia appears significantly higher in children with MUS, with respect to healthy controls, only when assessed through self-report questionnaires and not when investigated with objective tasks of identification of one’s own emotions (Hadji-Michael et al, 2019). In this study, alexithymia was only investigated with the self-report questionnaire TAS-20, where only two subjects scored above the cut off.…”
Section: Discussionmentioning
confidence: 99%